Effect of citrulline on post-exercise rating of perceived exertion, muscle soreness, and blood lactate levels: A systematic review and meta-analysis - Rhim, H. C.; Kim, S. J.; Park, J.; Jang, K.-M. (Journal of Sport and Health Science, 2020)
Highlights: Citrulline supplements are effective in reducing post-exercise rating of perceived exertion (RPE) and muscle soreness. A total of 3-4 g of L-citrulline or 8 g citrulline malate (CM) are recommended 1 h before exercise. Citrulline supplements are especially recommended for power and strength athletes for them to adequately recover and subsequently train at their desired intensity level.